Evaluation of the adverse effects of oral firocoxib in healthy dogs - Steagall, P. V. M.; Mantovani, F. B.; Ferreira, T. H.; Salcedo, E. S.; Moutinho, F. Q.; Luna, Stélio Pacca Loureiro [UNESP] (Blackwell Publishing, 2007)
This study evaluated the adverse effects of oral firocoxib in dogs. Six dogs (20.2 +/- 6.3 kg) were studied. Values for complete blood count (CBC), serum urea, creatinine, alanine transaminase, alanine phosphatase, -glutamyl transferase, occult blood in feces, platelet aggregation, and buccal mucosal bleeding time were measured before and 7, 14, 21, and 29 days after SID treatment with firocoxib 5.3 +/- 0.34 mg/kg (FG) or lactose 1 mg/kg (LG) for 2 8 days, in a randomized crossover study. Gastrointestinal (GI) tract endoscopy was performed before treatment began and at 29 days. Lesions were scored from grade 0 to 6. Data were analyzed using ANOVA and paired t-tests (P < 0.05). None of the dogs presented adverse clinical effects. There were no significant changes in CBC, biochemical profiles within groups, or differences between groups. Pretreatment mean SD bleeding time (LG, 70.7 +/- 32.1 sec; FG, 75.8 +/- 38.1 sec) and platelet aggregation (LG, 86.4 +/- 10.2%; FG, 85.6 +/- 9.2%) were not significantly different from readings at 29 days (LG, 95.2 +/- 25 sec; FG, 91.7 +/- 24 sec and LG, 73.2 +/- 15.1%; FG, 84 +/- 10.3%) nor the groups were different. None of the dogs had positive fecal occult blood tests, and endoscopic lesion scores were grade 0 both before treatment and at 29 days. Administration of firocoxib did not cause any adverse effects on GI, or hematological or serum biochemical variables and appears to have been well tolerated by dogs.